Membrane separation processes for dehydration of bioethanol from fermentation broths: Recent developments, challenges, and prospects. (May 2019) - Khalid, Azqa; Aslam, Muhammad; Qyyum, Muhammad Abdul; Faisal, Abrar; Khan, Asim Laeeq; Ahmed, Faisal; Lee, Moonyong; Kim, Jeonghwan; Jang, Nulee; Chang, In Seop; Bazmi, Aqeel Ahmed; Yasin, Muhammad
Abstract: Bioethanol has garnered a great interest as a potential energy source, mainly due to its sustainable and green nature. Generally, bioethanol is produced through the microbial conversion of biomass and biomass derived syngas. However, the dehydration and purification steps for achieving fuel-grade ethanol from the microbial production process consume tremendous amounts of energy. This high energy consumption limits the feasibility of microbial ethanol production on the commercial scale. In this context, selection of an optimal technology for product separation is essential for successful commercialization of microbially produced bioethanol. This article presents the recent developments in dehydration and purification technologies for bioethanol production using distillation and membrane based separation. Distillation and pervaporation are analyzed on the basis of the overall energy requirement, consumption, and economics. Pervaporation-assisted distillation approaches are also examined from the perspective of process systems engineering, including factors affecting the system performance. Furthermore, the role of simulation in technological development along with available mathematical models is discussed, and commercial status of pervaporation based separation is presented. Finally, the current status of the existing technology, challenges, and future research directions are identified from the perspective of achieving process sustainability on the industrial scale. Economic comparison between distillation and different hybrid schemes revealed that integrating distillation with membrane based separation techniques reduce the bioethanol production cost. Moreover, hybrid schemes that combine distillation with pervaporation, and steam stripping with vapor permeation are proved to be the best combinations for the cheapest bioethanol production. Graphical abstract: fx1 Highlights: Recent developments in dehydration of bioethanol are presented. Conventional and membrane-based technologies are compared. Integrating pervaporation with distillation reduce the bioethanol production cost. The most economical hybrid schemes for bioethanol separation is identified. Operational optimization and thermodynamic evaluation of hybrid processes are required.